Strategi Ustadz dalam Meningkatkan dan Menjaga Hafalan Alquran Santri di Pondok Pesantren - Akhsanudin, M. (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
Memorizing the Qur'an is one form of human effort to get closer to Allah through His words. This research uses a qualitative approach with descriptive research and case studies to explore the Ustadz's strategy in improving and maintaining students' memorization of the Alquran at the Darullughah IV Islamic Boarding School. The results of this research are careful planning, which includes memorization methods, memorization maintenance, memorization targets, and strategies for overcoming obstacles. The mutqin method used has been proven effective in helping students memorize the Koran properly and correctly. Efforts to maintain memorization through muraja'ah, tasmi' programs, and other repetition strategies have helped students maintain and strengthen their memorization. Apart from that, teaching about tahsin has also improved the quality of reading the Koran in class, by ensuring that students read correctly according to the rules of tajwid.